Hubungan antara Dukungan Keluarga dengan Respon Sosial pada Lansia di Desa Sokaraja Lor Kecamatan Sokaraja - Nusi, Ferani; Wijayanti, Rahayu; Rahayu, Eva (Jurnal Keperawatan Soedirman, 2010)
Generally, the physical condition after entering elderly period is experienced decreasing. Changes in elderly generally directed to physical and psychics healthy decreasing and finally will influence on their economic and social activity. Support from elderly family is highly influenced on social relationship of elderly. The objective of the research was to know the correlation between family support with social responses in elderly at Sokaraja Lor Village of Sokaraja Subdistrict. This research used cross sectional method. The samples in this research were 75 peoples. Data analysis method used frequency distribution and Chi Square. The result of this research showed that most of elderly who is accomplished as research sample were in age of 60-65 and 71-75, were 21 people (28,0%), junior high school and its same level were 42 peoples (56,0%), javaness and jobless, women were 44 peoples (58,7%) and widowers were 40 peoples (53,3%). All of respondents were Moslem. Family support that were categorized as non effective were 37 respondents (49,3%) while family support that were categorized as effective were 38 respondents (50,7%). The level of elderly evidence who were getting social active responses were 36 peoples (48,0%), while elderly who were getting passive social responses were 39 peoples (52,0%). The result of family support variable with social responses showed significant correlation, there were family support through communication (p=0,000), family emotional support (p=0,000), social interaction support (p=0,000), financial support (p=0,002), support in supplying transportation (p=0,001), support through the effort of maintaining physical activity which could still done by elderly (p=0,002). For the analysis result of family support variable with social response which was showed no significant correlation was family support in supplying food (p=0,219). There was significant correlation between family support with social responses in elderly at Sokaraja Lor Village of Sokaraja Subdistrict (p=0,000).